Studi Kualitatif Strategi Koping Penderita HIV AIDS di Kota Bandung - Salami Salami; Annisa Ayu Muvira; Perla Yualita (Faletehan Health Journal, 2021)
HIV/AIDS is a chronic disease that causes negative impacts in the form of physical, psychological, social, and spiritual problems that subsequently lead people living with HIV/AIDS to live a stressful life. Negative issue and stigmatization issues are also sources of pressure experienced by survivors. They may result in psychiatric disorders which require survivors to have adaptive coping mechanisms. Coping strategies determine an individual’s success in overcoming the pressure. This study aimed to explore coping strategies among survivors by using a qualitative descriptive research method. Interactive analysis model by Miles and Huberman was utilized as the data analysis technique. The data were obtained through semi in-depth interviews which involved 6 participants who were selected by purposive sampling. A total of 6 themes were obtained, namely resignation to God, unwilling to assume about the illness, diversion of problems, attempts of rising up, efforts to overcome problems, and concealment of health status. The researchers concluded that the six participants had a tendency to apply emotion-focused coping techniques. Nurses are therefore recommended to employ intervention strategies by providing counselling and education to people living with HIV/AIDS and their family.